Psychologie du sexisme : des stéréotypes de genre au harcèlement sexuel - Faniko, Klea; Dardenne, Benoit (Collection Ouvertures psychologiques. LMD, 2021)
"Depuis plusieurs années et sous l'impulsion de mouvements sociaux comme #MeToo, de nombreuses affaires de violences sexistes et sexuelles, impliquant des personnalités publiques ou des institutions connues, éclatent au grand jour dans les médias. Ces différents témoignages de femmes mettent en lumière l'ampleur des violences sexistes et sexuelles dans le monde. Comment expliquer une telle prévalence? Quels processus psychologiques peuvent conduire à l'apparition de stéréotypes, de préjugés et de discriminations sexistes? L'objectif de cet ouvrage, rassemblant 45 chercheurs francophones, est de contribuer à la compréhension des conséquences des discriminations sexistes, mais surtout d'aider à décrypter leurs mécanismes. Le phénomène s'avère complexe et très souvent subtil, prenant diverses formes et étant profondément inscrit dans les rouages de la société et des rapports humains. En plus des analyses présentées dans l'ouvrage, différentes pistes d'action sont proposées pour les entreprises et les institutions souhaitant promouvoir un environnement de travail inclusif."--Quatrième de couverture.
Keywords: EDI; approches et analyses; cours; discipline; discours dominant; discriminations; harcèlement sexuel; outils; outils didactiques; premier cycle; psy4910; psychologie; sciences humaines; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; violences

Sex & gender: An introduction - Lips, Hilary M. (Waveland Press, Inc., 2020)
Are sex and gender really two different things? How malleable is gender identity? Do both gender and sex have to be conceptualized as binaries—as having two distinct but complementary categories? Should we emphasize gender differences, or is that the wrong question? When should we call a gender difference “small”? Are women really “nonaggressive” or does that label stem from stereotyping? How does subtle or “modern” sexism work on its targets? Scholarship on these and other gender-related questions has exploded in recent years. Hilary Lips synthesizes that research for students in an accessible and readable way. Concepts on sex and gender are presented with the social context in which they were developed. As in previous editions, Lips takes a multicultural approach, discussing the gender experiences of people from a wide range of races, cultures, socioeconomic statuses, and gender and sexual identities. She emphasizes empirical research but takes a critical approach to that research.
Keywords: analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; construction du savoir; corps; cours; discipline; discours dominant; essentialisation; hétérosexisme; identité; identité sexuelle; inégalités; premier cycle; psy4910; psychologie; santé; sciences humaines; sexe/genre; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; trs3550; études de genres

Companion to sexuality studies - Naples, Nancy A. (Wiley-Blackwell companions to sociology, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités

The future of sex and gender in psychology: Five challenges to the gender binary - Hyde, Janet Shibley; Bigler, Rebecca S.; Joel, Daphna; Tate, Charlotte Chucky; van Anders, Sari M. (American Psychologist, 2019)
The view that humans comprise only two types of beings, women and men, a framework that is sometimes referred to as the “gender binary,” played a profound role in shaping the history of psychological science. In recent years, serious challenges to the gender binary have arisen from both academic research and social activism. This review describes 5 sets of empirical findings, spanning multiple disciplines, that fundamentally undermine the gender binary. These sources of evidence include neuroscience findings that refute sexual dimorphism of the human brain; behavioral neuroendocrinology findings that challenge the notion of genetically fixed, nonoverlapping, sexually dimorphic hormonal systems; psychological findings that highlight the similarities between men and women; psychological research on transgender and nonbinary individuals’ identities and experiences; and developmental research suggesting that the tendency to view gender/sex as a meaningful, binary category is culturally determined and malleable. Costs associated with reliance on the gender binary and recommendations for future research, as well as clinical practice, are outlined. (PsycINFO Database Record (c) 2019 APA, all rights reserved).
Keywords: LGBTQIA2+; activisme; analyse critique; approches et analyses; cours; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; queer; revue de la littérature; sciences humaines; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; études de genres

Gender: Psychological perspectives - Brannon, Linda (Routledge, 2017)
"Gender: Psychological Perspectives" synthesizes the latest research on gender to help students think critically about the differences between research findings and stereotypes, provoking them to examine and revise their own preconceptions. The text examines the behavioral, biological, and social contexts in which women and men express gendered behaviors. The text's unique pedagogical program helps students understand the portrayal of gender in the media and the application of gender research in the real world. -- From publisher's description. Contenu : Preface -- Acknowledgements -- About the author -- The study of gender -- Researching sex and gender -- Gender stereotypes: masculinity and femininity -- Hormones and chromosomes -- Theories of gender development -- Developing gender identity -- Intelligence and cognitive abilities -- Emotion -- Relationships -- Sexuality -- School -- Careers and work -- Health and fitness -- Stress, coping, and psychopathology -- Treatment for mental disorders -- How different? -- References -- Index.
Keywords: approches et analyses; biologie; comportements sexuels; cours; différence des sexes; discipline; discours dominant; identité sexuelle; maternité; paternité; premier cycle; psy4910; psychologie; relations amoureuses; santé; santé mentale; sciences; sciences humaines; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences sexuelles; études de genres

Le rose et le bleu : la fabrique du féminin et du masculin - Beauvalet-Boutouyrie, Scarlett; Berthiaud, Emmanuelle (Collection Histoire (Paris. 2013), 2016)
Une histoire de l'étude biologique, des statuts, des droits, de l'éducation, des apparences et des rôles attendus des hommes et des femmes, du XVIe au XXIe siècle, qui interroge la fabrication des concepts de masculin et de féminin.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; approches et analyses; cours; discipline; histoire; histoire et politique; postmodernisme; premier cycle; psy4910; psychologie; périodes historiques; sciences humaines; sexe/genre; stéréotypes de genre; thématiques; études de genres

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Genre et psychanalyse : la différence des sexes en question - Rassial, Jean-Jacques; Chevalier, Fanny; Colloque Genre et psychanalyse (Érès poche, 2016)
« La remise en cause de l’évidence naturelle jusque-là accordée à la différence des sexes occupe la scène des débats publics et se retrouve théorisée par l’émergence du concept de « genre » dans sa distinction d’avec le sexe. La différenciation entre sexe et genre émerge d’une fracture avec l’idée que le sexe biologique déterminerait l’identité sexuée et sexuelle. Dans cette nouvelle terminologie, le sexe ne renvoie plus alors qu’à la dimension anatomique et biologique tandis que le genre réfère à la construction psychologique et sociale du sexe. Malgré la pluralité des théories auxquelles le genre a donné naissance, l’émergence de cette notion prend en compte que sexe anatomique, sexuation psychique et sexualité peuvent trouver des nouages autres que ceux promus par des normes confondues avec l’ordre naturel – nouage, souligne la psychanalyse, radicalement singulier pour chacun. Cet ouvrage propose une introduction à toute la complexité de ces questions. Il axe son propos sur les controverses entre les théories psychanalytiques et les études sur le genre, et ouvre le dialogue à la littérature, à la philosophie et au cinéma. Cette perspective pluridisciplinaire reflète ainsi l’hétérogénéité des différents abords et usages du genre. »-- Résumé de l'éditeur.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; cours; discipline; genre; identité sexuelle; identités LGBTQIA2+; post-structuralisme; premier cycle; psy4910; psychanalyse; psychologie; périodes historiques; ressource en ligne; sciences; sciences humaines; sexe/genre; thématiques

Pornography, feminist views of - Davis, Berta (The International Encyclopedia of Human Sexuality, 2015)
Feminist women's attitudes toward pornography are significantly polarized. Anti‐porn feminists have taken a position that pornography is degrading toward women, leads to distortion of healthy male‐female sexuality, leads to distorted images of the female body, increases male anxiety about sexual adequacy, sexual compulsivity, and increase violence toward women including rape and sexual harassment.
Keywords: approches et analyses; cours; discipline; féminisme anti-porn; féminisme pop; pornography; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; thématiques

Mon corps a-t-il un sexe? Sur le genre, dialogues entre biologies et sciences sociales - Gonthier, Josiane; Ruppli-Coursange, Mireille (Recherches (Paris. 1994), 2015)
"Sexe" est l'un des mots de la langue française que les gens sans distinction de classe, de religion, d'apparence ou de profession, utilisent avec grand intérêt, qu'ils soient accoudés au zinc d'un bistrot ou à la paillasse d'un laboratoire de biologie moléculaire. Deux mises en scène distinctes, sociale ou scientifique ; deux scénarios différents : d'un côté, les histoires d'amour ou d'imaginaire sexuel, de l'autre, les recherches biologiques. Sous ce mot de "sexe", notre langue, si riche, produit une polysémie bien fâcheuse. L'ambition de ce volume, qui rassemble les contributions de chercheurs et chercheuses en sciences de la vie et en sciences humaines et sociales est de faire le point sur les connaissances concernant le sexe biologique et ses variations, dont on sait désormais qu'il ne permet pas de séparer les individus en deux catégories bien distinctes. Ce livre veut aussi évaluer l'impact du genre sur le développement du corps des êtres sexués et sur la construction de leur identité. Enfin, il cherche à apprécier dans quelle mesure les croyances liées au genre (bicatégorisation mâle-femelle stricte, supériorité masculine) ont pu influencer les recherches menées sur le sexe biologique. Et les témoignages de personnes intersexes et transgenres apportent sur la question de l'identité sexuée un éclairage complémentaire qui bouscule les "réponses" que donnent le plus souvent la médecine et le droit.
Keywords: approches et analyses; biologie; corps; cours; discipline; discours dominant; premier cycle; psy4910; psychologie; pédagogie; queer; sciences; sciences humaines; sciences sociales; sexualité; systèmes d'oppressions; thématiques; épistémologie; études de genres

Dis/ability studies: theorising disablism and ableism - Goodley, Dan (Routledge, 2014)
In this ground-breaking new work, Dan Goodley makes the case for a novel, distinct, intellectual, and political project – dis/ability studies – an orientation that might encourage us to think again about the phenomena of disability and ability. Drawing on a range of interdisciplinary areas, including sociology, psychology, education, policy and cultural studies, this much needed text takes the most topical and important issues in critical disability theory, and pushes them into new theoretical territory. Goodley argues that we are entering a time of dis/ability studies, when both categories of disability and ability require expanding upon as a response to the global politics of neoliberal capitalism. Divided into two parts, the first section traces the dual processes of ableism and disablism, suggesting that one cannot exist without the other, and makes the case for a research-driven and intersectional analysis of dis/ability. The second section applies this new analytical framework to a range of critical topics, including: The biopolitics of dis/ability and debility Inclusive education Psychopathology Markets, communities and civil society. Dis/ability Studies provides much needed depth, texture and analysis in this emerging discipline. This accessible text will appeal to students and researchers of disability across a range of disciplines, as well as disability activists, policymakers, and practitioners working directly with disabled people.
Keywords: EDI; approches et analyses; capacitisme; care; corps; cours; discipline; interdisciplinarité; lit4700; premier cycle; psychologie; pédagogie; santé; sciences de l'éducation; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles

Un texte théorique libérateur - Molinier, Pascale; Fausto-Sterling, Anne (Les cinq sexes : pourquoi mâle et femelle ne sont pas suffisants, 2013)
Keywords: approches et analyses; cours; discipline; fem1000; premier cycle; psychologie; sciences humaines; sexe biologique; sexisme; systèmes d'oppressions

Cerveau, hormones et sexe : des différences en question - Cossette, Louise (Les éditions du remue-ménage, 2012)
Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d’ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l’information diffusée tient davantage du préjugé, du parti pris idéologique, que d’une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd’hui encore ?C’est de ce constat, et d’un certain sentiment d’exaspération, qu’est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S’appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l’orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d’auteures féministes. Il ne s’agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ? Des textes de Line Chamberland, professeure au département de sexologie de l’UQAM et titulaire de la Chaire de recherche sur l’homophobie de l’UQAM ; Louise Cossette, professeure au département de psychologie de l’UQAM et membre de l’Institut de recherches et d’études féministes (IREF) de l’UQAM ; Chantal Maillé, professeure à l’Institut Simone de Beauvoir à l’Université Concordia et Catherine Vidal, neurobiologiste, directrice de recherche à l’Institut Pasteur de Paris.
Keywords: Brain; Human behavior; LGBTQIA2+; Men; Psychology; Sex differences; Sex differences (Psychology); Women; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem7000; genre; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lit3220; premier cycle; psy4910; psychologie; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sexualité; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

The Sexualisation of Culture? - Gill, Rosalind (Social and Personality Psychology Compass, 2012)
This article examines contemporary debates about the ‘sexualisation of culture’. It sets out the context for claims that Western societies are becoming more sexualised and it explores a number of competing perspectives about sexualisation. It then looks in more detail at the nature of claims about sexualisation as they emerge from the different disciplinary perspectives of Psychology and Media and Cultural Studies, contrasting the strengths and weaknesses of each, and raising criticisms of both. In a final discussion section, the article considers the usefulness or otherwise of the notion of ‘sexualisation’ as analytic category and points to the need to go beyond polarised positions. It advocates a psychosocial approach that takes seriously differences and power in considering the contemporary proliferation of ‘sexualised’ images, practices and media
Keywords: approches et analyses; communication; corps; cours; discipline; discours dominant; discours médiatique; féminisme pop; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; systèmes d'oppressions; thématiques; études culturelles

Cerveau, sexe et préjugés - Vidal, Catherine (Cerveau, hormones et sexe: Des différences en question, 2012)
"Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d'ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l'information diffusée tient davantage du préjugé, du parti pris idéologique, que d'une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd'hui encore ? C'est de ce constat, et d'un certain sentiment d'exaspération, qu'est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S'appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l'orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d'auteures féministes. Il ne s'agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ?"--Page 4 de la couverture.
Keywords: amériques; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; discipline; discours dominant; fem1000; hétéronormativité; hétérosexisme; neurobiologie; neuropsychologie; pol4102; premier cycle; psy4910; psychologie; québec; régions géographiques; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

Brain storm: The flaws in the science of sex differences - Jordan-Young, Rebecca M. (Harvard University Press, 2010)
Jordan-Young has written a stunning book that demolishes most of the science associated with the dominant paradigm of the development of sex and gender identity, behavior, and orientation. The current paradigm, brain organization theory, proposes: "Because of early exposure to different sex hormones, males and females have different brains"; and these hormones also create "gay" and "straight" brains. Jordan-Young interviewed virtually every major researcher in the field and reviewed hundreds of published scientific papers. Her conclusion: "Brain organization theory is little more than an elaboration of longstanding folk tales about antagonistic male and female essences and how they connect to antagonistic male and female natures." She explains, in exquisite detail, the flaws in the underlying science, from experimental designs that make no statistical sense to "conceptually sloppy" definitions of male and female sexuality, contradictory results, and the social construction of normality. Her conclusion that the patterns we see are far more complicated than previously believed and due to a wider range of variables will shake up the research community and alter public perception.
Keywords: LGBTQIA2+; analyse critique; approches et analyses; corps; cours; différence des sexes; discipline; discours dominant; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; revue de la littérature; sciences; sciences humaines; sexe/genre; sexisme; sociologie; systèmes d'oppressions; thématiques

Intimate Justice: A Critical Analysis of Sexual Satisfaction - McClelland, Sara I. (Social and Personality Psychology Compass, 2010)
This article elaborates an intimate justice framework to help guide research on sexual satisfaction. Using a critical historiography approach, I examine the etiology and development of the psychological construct of “satisfaction” over the last century and argue that social and political antecedents to satisfaction ratings are an essential and under-theorized aspect of research in this field. By examining what are considered to be the most influential definitions in life satisfaction research, I identify conceptual gaps, oversights, and disagreements that characterize this body of work, and specifically its theoretical treatment of inequity. Moving to the intimate domain, I argue that the field of sexual satisfaction must include theories and methods that systematically consider the role of social and sexual stigmas as antecedents to sexual satisfaction ratings. In the conclusion, building from existing social justice theories, I propose an intimate justice framework as a means to guide research that can highlight issues of entitlement and deservingness in sexual satisfaction research. This is particularly important as sexual satisfaction is increasingly used as an indicator of individual and relational well-being; however, this construct is presently limited and inadequately measured for women and men who experience limited sexual rights in the socio-political domain because of their gender and/or sexual minority status.
Keywords: approches et analyses; capacitisme; cours; discipline; intersectionnalité; justice sociale; premier cycle; psychologie; racisme; ressource en ligne; sciences humaines; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques

Ethnic, Gender, and Acculturation Influences on Sexual Behaviors - Meston, Cindy M.; Ahrold, Tierney (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
Much research has been conducted on ethnic differences in sexuality, but few studies have systematically assessed the importance of acculturation in sexual behavior. The present study assessed general differences in normative sexual practices in healthy Euro-American, Asian, and Hispanic populations, using measures of acculturation to analyze the relative effects of heritage and mainstream cultures within each group. A total of 1,419 undergraduates (67% Euro-American, 17% Hispanic, 16% Asian; 33% men, 67% women) completed questionnaires which assessed sexual experience and causal sexual behaviors. In concordance with previous studies, Asians reported more conservative levels of sexual experience and frequency of sexual behaviors, fewer lifetime partners, and later ages of sexual debut than Euro-American or Hispanic counterparts. Hispanic reported sexual experiences similar to that of Euro-Americans. There was a significant interaction between mainstream and heritage acculturation in predicting number of lifetime sexual partners in Asian women such that the relationship between heritage acculturation and casual sexual behavior was stronger at lower levels of mainstream acculturation. On the other hand, in Hispanic men, higher levels of mainstream acculturation predicted more casual sexual behavior (one-time sexual encounters and number of lifetime sexual partners) when heritage acculturation was low but less casual sexual behavior when heritage acculturation was high. These results suggest that, for sexual behavior, Hispanic men follow an “ethnogenesis” model of acculturation while Asian women follow an “assimilation” model of acculturation.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexualité; thématiques; états-unis

Diversité sexuelle et constructions de genre - Chamberland, Line; Frank, Blye W.; Ristock, Janice L. (Collection Santé et societé, 2009)
Les sciences sociales et épidémiologiques contemporaines tendent de plus en plus à prendre en compte la question du genre dans leurs théories sur les orientations sexuelles. Elle mettent ainsi en évidence les diverses articulations entre les formes de sexisme et d'homophobie, et leurs impacts différenciés selon les constructions du genre et les orientations sexuelles, de même qu'en fonction du contexte socioculturel dans lequel elles se situent. Réalisé avec l'appui de l'équipe pancanadienne Sexualités et genres, vulnérabilité et résilience (SVR), cet ouvrage regroupe des contributions de chercheurs francophones et anglophones du Québec, du Canada, de la France et de la Suisse romande, qui examinent les dimensions socioéconomiques, progessionnelles, familiales, relationnelles et psychologiques afin de saisir les variations liées au genre au sein des minorités sexuelles. Faisant appel à des résultats de travaux multidisciplinaires qui s'appuient sur des méthodologies de types quantitatif et qualitatif, ce livre met en lumière des processus contribuant aux inégalités sociales dans les champs de l'éducation, de l'économie et de la santé, et à des condition de vulnérabilité qui affectent l'estime de soi, les réseaux de soutien et la vie sociale. Les recherches observent des modes de résilience significatifs qui, là encore, peuvent varier en fonction du genre, suggérent ainsi sa prise en compte dans les interventions.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; lesbophobie; premier cycle; psy4910; psychologie; rapports sociaux de sexe; ressource en ligne; sciences humaines; sciences sociales; sexe/genre; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; théorie du genre; épistémologie; études de genres

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Intersections: cultures, sexualités et genres - Brotman, Shari L.; Lévy, Joseph J. (Collection Santé et société, 2008)
Les intersections entre la culture, le genre et la sexualité retiennent aujourd’hui l’attention des chercheurs qui travaillent sur la diversité sexuelle, une tendance que l’on rencontre dans l’espace québécois et canadien. Plusieurs études ont ainsi porté sur ces enjeux parmi les autochtones et les groupes ethnoculturels. Cet ouvrage collectif, réalisé par des chercheurs, anglophones et francophones, de l’équipe pancanadienne Sexualités, Vulnérabilités et Résilience, présente ainsi un ensemble de travaux qui font le point sur ces questions. Les dimensions théoriques et méthodologiques sont ainsi cernées et des études empiriques, faisant appel à des approches quantitatives et qualitatives, traitent des trajectoires et des identités parmi différentes populations, des problèmes de santé auxquels elles peuvent être confrontées et des variations dans les usages sociosexuels d’Internet. Ce tour d’horizon aide à mieux comprendre la complexité des intersections touchant les identités sexuelles et les dimensions culturelles et suggère des pistes de recherche et d’intervention à développer.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; identités LGBTQIA2+; intersectionnalité; premier cycle; psychologie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexologie; sexualité; thématiques; travail social

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Une voix différente : pour une éthique du care - Gilligan, Carol (Flammarion, 2008)
La morale a-t-elle un sexe ? Les femmes et les hommes ont-ils un sens différent de la moralité ? Une telle question donne la mesure de l'immense débat qu'a suscité le livre de Carol Gilligan, catalyseur des réflexions féministes sur l'éthique du care (imparfaitement traduit par " sollicitude "). Si les analyses en termes de genre sont désormais connues, l'idée de care n'a pas rencontré un aussi large accueil. L'intérêt public grandissant pour les questions d'aide aux personnes vulnérables, et pour les problèmes sociaux et politiques engendrés par la situation inégalitaire des travailleuses/eurs du care et leur circulation au niveau mondial, a permis que les questions théoriques liées au care trouvent une nouvelle pertinence. Il a fallu également que se dissipe le rapport ombrageux du féminisme aux questions morales pour que le care ne soit pas rabattu sur l'idée d'un " service " contraint au profit des plus puissants. Aux Etats-Unis, Une voix différente est le texte le plus lu et le plus cité de la " seconde vague " du féminisme. Il a ouvert un débat politique crucial, entre éthique de la justice et éthique du care, entre une moralité centrée sur l'équité, l'impartialité et l'autonomie et une moralité formulée " d'une voix différente ", reconnue le plus souvent dans l'expérience des femmes, et fondée non sur des principes mais sur une question : comment faire, dans une situation donnée, pour préserver et entretenir les relations humaines qui y sont en jeu ?
Keywords: 1900-1999; amériques; care; cours; discipline; fem1000; har4600; phi4336; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis; éthique

The Politics of Protection: Body Image, Social Pressures, and the Misrepresentation of Young Black Women - Poran, Maya A. (Sex Roles : A Journal of Research, 2006)
As part of a larger multi-method study, 15 Black women college students participated in focus group discussions on the body. Contrary to popular theories that propose that Black women are protected by a “Black Culture” that buffers them from negative effects of body representations—thereby leaving them with higher body esteem—the themes that emerged in the focus group discussions indicate that young Black women are indeed feeling (1) pressures to be thin, (2) pressures from the preferences of men of diverse ethnicities, (3) competition with other Black women in the realms of beauty, and (4) a strong sense of being misrepresented by media images of thin Black women. These results not only indicate that body image issues are of real pressing concern to young Black women, but that psychological research methodologies may be adding to the misrepresentation of young Black women and their struggles. Qualitative methods must be utilized in order to hear more clearly the voices of Women of Color.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; image corporelle; intersectionnalité; new york; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; états-unis

Grossesse hors mariage dans les familles haïtiennes - Raphaël, Frantz (Santé mentale au Québec, 2006)
Des grossesses précoces chez des jeunes adolescentes haïtiennes de Montréal entraînent des situations de crise qui touchent plusieurs familles, en plus d’interpeller et d’impliquer des intervenants de diverses disciplines. Le sujet, abordé dans un contexte transculturel, fait référence au biculturalisme haïtien, tant en Haïti qu’en terre étrangère. Dans cet article, l’auteur aborde plus particulièrement la situation des Haïtiens dans le contexte québécois. L’analyse de l’attitude des parents des deux groupes culturels, occidentalisé et créole, constitue une lumière médiatrice dans les relations d’aide ou d’intervention psychothérapeutique. Dans la communauté haïtienne, les problèmes d’identité culturelle d’une part, et, le manque d’affiliation à la famille, d’autre part, sont à la base des conflits entre parents et enfants. L’auteur conclut avec des propositions dans le but d’améliorer l’efficacité des interventions avec ces familles dans leur processus d’adaptation migratoire.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; conflit familial; cours; discipline; grossesse hors mariage; haïti; justice sociale; maternité; montréal; premier cycle; psychologie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; thématiques

Cerveau, sexe et pouvoir - Vidal, Catherine; Benoit-Browaeys, Dorothée. (Regards, 2005)
À la lumière des connaissances actuelles en neurosciences, on serait tenté de croire que les vieux préjugés sur les différences biologiques entre les hommes et les femmes ont été balayés. Ce n'est manifestement pas le cas : médias et ouvrages de vulgarisation prétendent que les femmes sont " naturellement " bavardes et incapables de lire une carte routière, tandis que les hommes sont nés bons en maths et compétitifs. Ces discours laissent croire que nos aptitudes, nos émotions, nos valeurs sont tablées dans des structures mentales immuables depuis les temps préhistoriques. Cet ouvrage, qui s'adresse à un large public, replace le débat autour de la différence des sexes sur un terrain scientifique rigoureux, au-delà des idées reçues. L'enjeu est de comprendre le rôle de la biologie, mais aussi l'influence de l'environnement social et culturel dans la construction de nos identités d'hommes et de femmes. Notre destin n'est pas inscrit dans notre cerveau! [Source : d'après la 4e de couv.].
Keywords: 2000 à aujourd'hui; approches et analyses; corps; cours; discipline; discours dominant; inégalités; neuropsychologie; neurosciences; premier cycle; psy4910; psychologie; périodes historiques; sciences; sciences humaines; sexe/genre; sexisme; systèmes d'oppressions; thématiques

Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques

The impact of culture and minority status on women's experience of domestic violence - Kasturirangan, Aarati; Krishnan, Sandhya; Riger, Stephanie (Trauma, violence & abuse, 2004)
The influence of culture and ethnic background on women’s experience of domestic violence has been explored in research only recently. Here the authors review research about the impact of culture and minority status in the United States on women’s experience of domestic violence, considering family structure,immigration, acculturation, oppression, and community response. The authors encourage researchers and service providers to acknowledge the effects on women of sociopolitical dynamics, including racism, and to identify specific aspects of culture that are relevant to intimate partner abuse.
Keywords: amériques; approches et analyses; cours; discipline; intersectionnalité; justice sociale; pauvreté; premier cycle; psychologie; racisme; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

Heterosexuals' use of "fag" and "queer" to deride one another: a contributor to heterosexism and stigma - Burn, S M (Journal of homosexuality, 2000)
This paper is on heterosexuals' use of words such as "fag" and "queer" to refer to one another in an insulting manner. This behavior perpetuates heterosexism and the stigmatization of gays. Two hundred and fifty-seven university students (73% Euro-American) served as participants. Males exhibited more anti-gay prejudice and anti-gay behavior than females. Heterosexual males frequently used words such as "fag" and "queer" to put one another down. Anti-homosexual prejudice was predictive of anti-gay behavior. However, approximately half of those who engaged in the behavior were not strongly anti-homosexual. For these individuals, the behavior may win approval from their social group. Awareness campaigns and peer reminders that the derisive use of "fag" and "queer" harms homosexuals may be effective in changing this group. It is more difficult to reduce this behavior in individuals with strong anti-homosexual attitudes. The role of individuals and educational and work organizations in bringing about change is discussed.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétérosexisme; insultes; premier cycle; psychologie; sciences humaines; soc2014; systèmes d'oppressions; thématiques

Life with the first baby: women's satisfaction with the division of roles - Cappuccini, G.; Cochrane, R. (Journal of Reproductive and Infant Psychology, 2000)
The ways parents divide their roles after their first child is born is a particularly complex arena. The success of negotiations within this close personal relationship may be central to the future of the new family. Women and their partners were surveyed in late pregnancy and 6 months after the birth. Their attitudes to role division remained largely non-traditional after the birth, even though most of them had incorporated some traditional elements into their behaviour. Emotional support received from their partners was important to women's satisfaction with role division, which had fallen only slightly after the birth. Eight of the women were interviewed in depth to explore why it might be that satisfaction with role division tended to remain high after the birth, despite the division usually not being what they had hoped for. Contributory factors may include changes in emphasis in the division of breadwinning and the maintenance of overall responsibility for traditional role areas despite sharing of tasks.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; europe; hétérosexualité; inégalités; maternité; premier cycle; privilèges; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques